DETERMINAN PEMANFAATAN PROGRAM PELAYANAN NIFAS SESUAI STANDAR KN3 DI PUSKESMAS NAGASWIDAK, PALEMBANG TAHUN 2017 - Purnamasari, Endah Widya (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2018)
Maternal Mortality Rate (MMR) is the health development success indicator of the health sector. In 2012 there were 43 maternal deaths with 18 deaths in the puerperium Palembang District. Postpartum maternal deaths could prevented by doing postnatal service. Based on data from Palembang District Health Office in 2016 coverage postpartum mothers in Nagaswidak Community Health Center 72,74% lower than target of 97% and even from year to year undergo a decline. This study aims to analyze related factors of postnatal visit in Nagaswidak community health center of Palembang. This study is analytic with cross sectional design. The samples were 51 postnatal women. Analysis of the data used is the Chi-square test (? = 0.05). The results of this study showed that there was a relationship between age, knowledge, attitudes, ease of transportation access, midwife participation and family support (p <0.05) and there was no correlation between education, employment, health service officer availability concierge services, and distance to access with postnatal visit.Keyword: Post Partum, Postnatal Visit